The Role of Religious Brand Community Support in Enhancing Value Co-Creation in Religio-Centric Markets: Case Study in Religious Tourism Destinations - Anita Kristina; Mohammad Sofyan Yasin (STAI Nurul Islam Mojokerto, 2026)
The urgency of this research stems from the phenomenon of religiously-based Packaged Drinking Water in tourism destinations, presenting a unique value co-creation model within Islamic economics. This study aims to analyze the role of religious brand community support in enhancing value co-creation for